Regulation of p53 by siRNA in radiation treated cells: Simulation studies - Puszyński, Krzysztof; Jaksik, Roman; Świerniak, Andrzej (1950- ) (Zielona Góra: Uniwersytet Zielonogórski)
Ionizing radiation activates a large variety of intracellular mechanisms responsible for maintaining appropriate cell functionality or activation of apoptosis which eliminates damaged cells from the population. The mechanism of such induced cellular death is widely used in radiotherapy in order to eliminate cancer cells, although in some cases it is highly limited by increased cellular radio-resistance due to aberrations in molecular regulation mechanisms of malignant cells.
Keywords: siRNA; p53; combined therapy